Case Report: A New Family With Pontocerebellar Hypoplasia 10 From Sudan - Amin, Mutaz; Vignal, Cedric; Hamed, Ahlam A. A.; Mohammed, Inaam N.; Elseed, Maha A.; Abubaker, Rayan; Bakhit, Yousuf; Babai, Arwa; Elbadi, Eman; Eltaraifee, Esraa; Mustafa, Doua; Yahia, Ashraf; et al. (Frontiers in Genetics, 2022)
Pontocerebellar hypoplasia type 10 (PCH10) is a very rare autosomal recessive neurodegenerative disease characterised by intellectual disability, microcephaly, severe developmental delay, pyramidal signs and mild cerebellar atrophy and white matter changes in brain Magnetic Resonance Imaging (MRI). The disease has been described in only twenty-one patients from ten Turkish families with a founder missense mutation in CLP1 gene which is involved in tRNA processing and maturation. We analysed three siblings from a consanguineous Sudanese family who presented with intellectual disability, dysmorphic features, developmental delay, and regression of milestones, microcephaly, epilepsy, extrapyramidal signs and mild pontine and cerebellar atrophy. We identified through whole exome sequencing the same mutation (c.419G>A; p.(Arg140His) that has been reported before in all Turkish families. Our study extends the phenotypes of PCH10 and reports for the first time cases with PCH10 from non-Turkish origin.